New perspectives in the model of stress response - Tonhajzerova, I; Mestanik, M (Physiological research, 2017)
The reactions of human organism to changes of internal or external environment termed as stress response have been at the center of interest during recent decades. Several theories were designed to describe the regulatory mechanisms which maintain the stability of vital physiological functions under conditions of threat or other environmental challenges. However, most of the models of stress reactivity were focused on specific aspects of the regulatory outcomes - physiological (e.g. neuroendocrine), psychological or behavioral regulation. Recently, a novel complex theory based on evolutionary and developmental biology has been introduced. The Adaptive Calibration Model of stress response employs a broad range of the findings from previous theories of stress and analyzes the responsivity to stress with respect to interindividual differences as a consequence of conditional adaptation - the ability to modify developmental trajectory to match the conditions of the social and physical environment. This review summarizes the contributions of the most important models in the field of stress response and emphasizes the importance of complex analysis of the psycho-physiological mechanisms. Moreover, it outlines the implications for nonpharmacological treatment of stress-related disorders with the application of biofeedback training as a promising tool based on voluntary modification of neurophysiological functions.
Keywords: Allostasis; Stress, Physiological; psychický stres; fyziologický stres; Stress, Psychological; zpětná vazba fyziologická; Animals; Humans; homeostáza; lidé; zvířata; Feedback, Physiological; Homeostasis; alostáza